Carotid Artery Stenting in Patients with Carotid Artery Stenosis - Hamid Sharif Khan, Asim Javed, Sohail Aziz, Muhammad Abdus Salam Azad, Ghulam Rasool (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate the effectiveness of carotid artery stenting in patients with carotid artery stenosis Methods: In this descriptive study rail roading technique was used for carotid artery stenosis. An 8F multipurpose guide was mounted over a 5F JB3 diagnostic catheter. The whole assembly was passed over the guide wire and finally multipurpose guide was slided into internal carotid artery. The lesion was crossed with an appropriate size distal protection device which was then deployed in internal carotid artery, distal to the lesion. Predilatation was performed with a 2- to 3-mm coronary balloon. The self expanding tapering carotid stent was placed across the lesion and deployed. Post dilatation, if required, was done by ensuring that at least 15-20% residual stenosis was left behind. Results: In a total of 108 carotid artery stenting procedures, average age was 66.66 years. Majority (80.5%) were male. Embolic protection device was used in all. Majority (96.3%) achieved technical success Conclusion: Carotid Artery stenting is an effective and safe treatment modality for internal carotid artery stenosis